2019
DOI: 10.1071/fp18291
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a rice vacuolar invertase isoform, OsINV2, for growth and yield-related traits

Abstract: OsINV2, a rice vacuolar invertase isoform, was assessed for its functional roles in plant growth and development with key focus on its agronomic traits such as grain weight, grain filling percentage, grain number and dry weights at various stages until harvest. Lack of differences between the wild-type and the mutants with respect to any of the aforementioned traits tested revealed a possibility of functional compensation of OsINV2 in the mutants conceivably by its isoform. This was confirmed by OsINV2 promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In our study, the double mutant INV3 KO INV2 KO showed a grain size smaller than both INV3 KO and INV2 KO (Figure 9), suggesting that in the absence of OsINV3, it is possible to detect a role of OsINV2 in the regulation of grain size. As reported previously, the functions of OsINV2 were redundantly encoded in OsINV3 [42]. Our results show for the first time that OsINV2 regulates grain size in the absence of OsINV3.…”
Section: Genetic Effect Between Osinv3 and Osinv2 In The Regulation Osupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, the double mutant INV3 KO INV2 KO showed a grain size smaller than both INV3 KO and INV2 KO (Figure 9), suggesting that in the absence of OsINV3, it is possible to detect a role of OsINV2 in the regulation of grain size. As reported previously, the functions of OsINV2 were redundantly encoded in OsINV3 [42]. Our results show for the first time that OsINV2 regulates grain size in the absence of OsINV3.…”
Section: Genetic Effect Between Osinv3 and Osinv2 In The Regulation Osupporting
confidence: 86%
“…Our results show that INV3 KO causes small grain size (Figures 5 and 6), suggesting that OsINV3 positively regulates grain size by causing cell expansion resulting in an increase in grain length and grain-width. Genetic data showed that INV2 KO did not cause any change in grain size by itself (Figures 8 and 9), but still plays important regulatory role in traits related to grain yield [42]. In our study, the double mutant INV3 KO INV2 KO showed a grain size smaller than both INV3 KO and INV2 KO (Figure 9), suggesting that in the absence of OsINV3, it is possible to detect a role of OsINV2 in the regulation of grain size.…”
Section: Genetic Effect Between Osinv3 and Osinv2 In The Regulation Omentioning
confidence: 42%
See 1 more Smart Citation
“…Our study identified OsINV2 as one of the candidate genes in MQTL 4.4 [contributed by QTLs qDPGWC, qPGWC, qWCR4.1, qWCR4.2, qch ( Peng et al., 2014a ; Wang et al., 2016 ; Yun et al., 2016 ; Edwards et al., 2017 )]. OsVIN2 and its homologue OsVIN3 regulate the sink size by controlling hexose to sucrose ratio and drive cell expansion by turgor generated due to influx of osmotic solutes ( Koch, 2004 ; Sergeeva et al., 2006 ; Morey et al., 2019 ). Consequently, vin2 and vin3 mutations lead to decreased seed size and shorter and lighter panicles ( Morey et al., 2018 ; Lee et al., 2019 ; Morey et al., 2019 ; Xu et al., 2019 ; Deng et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the sorghum genetic transformation efficiency is relatively lower, rice was selected as the receptor material to validate the function of SbSAI-2 gene in this study. Morey et al (2019) evaluated the functional role of rice soluble acid invertase isoform OsVIN2 in plant growth and development, studied the differences between important agronomic traits such as grain weight, grain filling rate, grain number and dry weight at various stages of growth and development, and found that there were no significant differences between the wild type and the mutant in terms of the agronomic traits tested. In the mutant, the non-structural carbohydrates in the stem will increase after the correct OsVIN2 gene was transformed, and the overexpression line has a higher number of spikelets, but the grain weight was reduced.…”
Section: Discussionmentioning
confidence: 99%